Pourquoi pas? Rational choice as a basic theory of HRM - Wenzel Matiaske (Management Revue, 2004)
A broad spectrum of theories from different disciplines is portrayed in contemporary HRM (as a discipline of business administration). Theories from psychology, sociology and economics correspond to the variety of problems addressed in HRM which are again situated at different levels of analysis, namely on the individual, group and organizational level. A narrow focus solely on economic approaches, as sometimes suggested in personnel economics, is therefore not sufficient. Instead, the contemporary 'rational choice' approach may serve as a 'new' basis for the discipline. The approach stems from economics and sociology and, as an offspring of these, combines elements of action and structure in its basic explanatory models. Also it is able to explain effects that emerge on the system or macro level. Indepth explanations allow model building at different levels of analysis, namely on an environmental, organizational and individual level, which can be seen as a major prerequisite of explanations in HRM. In addition 'rational choice' is conscious of the ignorance of its underlying action theory and this exposes it to the body of physiological and psychological knowledge. Anomalies of classic economic theory can therefore be restricted, for instance by using the method of decreasing abstraction. The method of decreasing abstraction serves as a basic principle or heuristic device for model building, in order to separate 'rational choice' from traditional anti-reductionism. This article introduces basic elements of the modern 'rational choice' approach: the macro-micro-macro model of explanation, homo socio-oeconomicus as a model of man and exchange theory as a baseline model of aggregation. A final summary discusses research questions and applications of 'rational choice' in HRM.
Keywords: 650; rational choice; economic sociology; micro-macro-link; homo socio-oeconomicus; Personalmanagement; Rationales Verhalten; Industriesoziologie